DETERMINATION OF ANALYTICAL CALCULATION ERROR OF MAGNETIC FIELD OF HIGH-VOLTAGE CABLE LINES WITH TWO-POINT BONDED CABLE SHIELDS CAUSED BY NON-UNIFORM CURRENT DISTRIBUTION IN THE SHIELDS - A. O. Tkachenko (National Technical University "Kharkiv Polytechnic Institute", 2017)
This paper deals with the determination of analytical calculation error of magnetic field of high-voltage cable lines in two-point bonded cable shields caused by non-uniformity of the current distribution in the shields. The relative error is determined by comparing numerical calculation of magnetic field obtained in the COMSOL Multiphysics software with the analytical one. It is shown that the maximum value of relative error does not exceed 8 %. The obtained error values are verified by testing the numerical calculation and confirmed by results of experiment. In paper proves the correctness of the analytical calculation of magnetic field of cable lines at the points of its normalization, which is carried out without taking into account the non-uniform current distribution in the cable shields.